History of Types and Length of Contraceptive Methods Use with Pre-Menopausal Complaints in Pre-Menopausal Women - Aisyatul R., Hana; Yudianti, Ika; Mas’udah, Endah Kamila (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Menopausal events are associated with decreased production of reproductive hormones, namely progesterone and estrogen. Both hormones in synthetic form are also present in some types of hormonal contraceptive methods. This study aims to determine the relationship between the history of the type of method and the length of use of contraceptives with the intensity of menopausal complaints. The design used is correlational analytics with a cross-sectional approach. A sample of 174 premenopausal women was selected by proportional random sampling. Information on the type and duration of contraceptive use was taken through interviews, and the intensity of premenopausal complaints was measured using the MRS (Menopause Rating Scale) questionnaire. Data analysis using regression methods was performed with STATA Statistics version 12.0, with statistical significance set at P < 0.05. Data analysis showed the associations between contraceptive types and pre-menopausal complaints (p-value 0.025) and between the length of contraceptive use and pre-menopausal complaints (p-value 0.021). The study recommends that contraceptive users consider the type and length of their methods, and healthcare providers should offer detailed counseling on how contraceptive choices might affect pre-menopausal symptoms. Future research should continue exploring the connection between contraceptive use and pre-menopausal complaints for more tailored guidance in the choice of contraceptive methods.